Toward Understanding Space-Charge Limited Current Measurements on Metal Halide Perovskites - Duijnstee, Elisabeth A; Ball, James M; Le Corre, Vincent Marc; Koster, L Jan Anton; Snaith, Henry J; Lim, Jongchul (ACS Energy Letters, 2020)
Metal halide perovskite semiconductors have sprung to the forefront of research into optoelectronic devices and materials, largely because of their remarkable photovoltaic efficiency records above 25% in single-junction devices and 28% in tandem solar cells, achieved within a decade of research. Despite this rapid progress, ionic conduction within the semiconductor still puzzles the community and can have a significant impact on all metal halide perovskite-based optoelectronic devices because of its influence upon electronic and optoelectronic processes. This phenomenon thus also makes the interpretation of electrical characterization techniques, which probe the fundamental properties of these materials, delicate and complex. For example, space-charge limited current measurements are widely used to probe defect densities and carrier mobilities in perovskites. However, the influence of mobile ions upon these measurements is significant but has yet to be considered. Here we report the effect of mobile ions upon electronic conductivity during space-charge limited current measurements of MAPbBr(3) single crystals and show that conventional interpretations deliver erroneous results. We introduce a pulsed-voltage space-charge limited current procedure to achieve reproducible current-voltage characteristics without hysteresis. From this revised pulsed current-voltage sweep, we elucidate a lower bound trap-density value of 2.8 +/- 1.8 x 10(12) cm(-3) in MAPbBr(3) single crystals. This work will lead to more accurate characterization of halide perovskite semiconductors and ultimately more effective device optimization.